FUZZY LOGIC FOR CONTROLLING SMOKE LEVEL ON SMART SMOKING ROOM - fajar pujiyanto; arief marwanto; suryani alifah (Journal of Telematics and Informatics, 2020)
Public space is one of the facilities that need in public areas. One of the public space facilities is a special smoking room. The existing smoking room is still conventional, meaning that there is without controlling system to maintain the air condition in the rooms. This study discusses a smart system to control air levels in smoking rooms based on fuzzy logic. Fuzzy analysis is carried out with input parameters, namely temperature, air humidity, CO levels, smoke levels and output parameters are supply fans, exhaust fans, and air ionizers. Based on the results of smart smoking model test compared wit the Matlab analysis, the Mean Squared Error (MSE) value on the supply fan = 0.0640, MSE on the exhaust fan = 0.0502 and MSE on the ionizer = 0.0604. The results for the MSE value are closed to zero, its means smart smoking rooms models is works properly.